Autophagy, citrullination and cancer - Durrant, LG (Taylor & Francis, 2016)
A cell needs to maintain a balance between biosynthesis and degradation of cellular components to maintain homeostasis. There are 2 pathways, the proteasome, which degrades short-lived proteins, and the autophagy/lysosomal pathway, which degrades long-lived proteins and organelles. Both of these pathways are also involved in antigen presentation or the effective delivery of peptides to MHC molecules for presentation to T cells. Autophagy (macroautophagy) is a key player in providing substantial sources of citrullinated peptides for loading onto MHC-II molecules to stimulate CD4(+) T cell responses. Stressful conditions in the tumor microenvironment induce autophagy in cancer cells as a mechanism to promote their survival. We therefore investigated if citrullinated peptides could stimulate CD4(+) T cell responses that would recognize these modifications produced during autophagy within tumor cells. Focusing on the intermediate filament protein VIM (vimentin), we generated citrullinated VIM peptides for immunization experiments in mice. Immunization with these peptides induced CD4(+) T cells in response to autophagic tumor targets. Remarkably, a single immunization with modified peptide, up to 14 d after tumor implant, resulted in long-term survival in 60% to 90% of animals with no associated toxicity. These results show how CD4(+) cells can mediate potent antitumor responses against modified self-epitopes presented on tumor cells, and they illustrate for the first time how the citrullinated peptides produced during autophagy may offer especially attractive vaccine targets for cancer therapy.